КАЗАХСТАНСКИЙ ОПЫТ ИНТРОДУКЦИИ ЛОШАДИ ПРЖЕВАЛЬСКОГО В ГОСУДАРСТВЕННОМ НАЦИОНАЛЬНОМ ПРИРОДНОМ ПАРКЕ «Алтын-Эмель» (Experimental biology, 2015)
There is description of 8 years old experience by introduction of Przewalski horse from Munich Zoo on the territory of National Nature Park "Altyn Emel". Also there are given characteristics of natural-climatic conditions ofpark and recommendations for improving of this work, analyzed main problems and difficulties of animal acclimatization.
Keywords: Przewalski horse